Feedlot performance and digestibility of beef steers fed steam flaked, popped, reconstituted and dry rolled sorghum grain - D.O. Yauk; C.L. Drake; R.R. Schalles (Kansas Agricultural Experiment Station Research Reports, 1971)
Because most finishing rations contain a high proportion of grain, better processing of sorghum grain to increase grain utilization should improve ration efficiency. Work in Texas, Oklahoma, Arizona, and Fort Hays has indicated that processing sorghum grain increased digestibility and utilization. This trial compared digestibility and feedlot performance of beef steers fed steam flaked, popped, reconstituted or dry-rolled sorghum grain.
Keywords: Cattlemen& #x27; s Day; 1971; Report of progress (Kansas State University. Agricultural Experiment Station); 546; Beef; Performance; Digestibility; Sorghum grain